Oximato-bridged copper(II) compounds: syntheses, molecular structures, magnetic, thermal and spectroscopic properties. Issue 15 (2nd August 2016) - Naskar, Jnan P.; Biswas, Chiranjan; Bandyopadhyay, Nirmalya; Walsh, James P. S.; Tuna, Floriana; Zhu, Miaoli; Lu, Liping
Abstract: Reaction of the Schiff base, 1-(4-methylimidazol-5-yl) phenylhydrazonopropane-2-one oxime (LH), with copper(II) perchlorate hexahydrate and copper(II) nitrate trihydrate in a 1 : 1 M proportion in methanol affords [Cu2 L2 (H2 O)(ClO4 )](ClO4 ) (1 ) and [Cu2 L2 (H2 O)2 ](NO3 )2 ] (2 ) in moderate yields. Both1 and2 have been characterized by elemental analysis, ESI-MS, FT-IR, UV–vis absorption spectroscopy, EPR, electric conductivity, and magnetic susceptibility measurements. The X-ray crystal structures of1·CH 3 COCH 3 and2 have been determined. Both compounds are dinuclear copper(II) complexes, with each copper μ 2 -bridged by two oxime ligands in a μ 2 - η 1, η 2 fashion. Variable temperature magnetic studies on1 and2 show that both compounds are dominated by an antiferromagnetic coupling through the oxime bridges. Abstract :